Podstawy strategii konkurencyjności rolnictwa polskiego - Kapusta, Franciszek (Background to the Competitive Strategies of Polish Agriculture, 2006)
Poland has an important position in the European Union in terms of its area and the population - 6th place, area of agricultural - use 3rd, the agricultural population and the professionally active population in the farming - 1st. The Polish farming is using low amounts of NPK and high level of natural fertilizers and is performing regular changes of plants. In the animal production it is based on country fodders and concentrates with the high participation of plant components. Everything creates its base of getting the good quality of agricultural production.In the production of agricultural basic commodities Poland takes high places in the European Union; to 8th. It is the biggest producer of cereal, including rye and oat, potatoes, and a significant producer of vegetables and fruit (4th place), and in the production of apples - 1st place, cow's milk; 4th place and meat 5th. This way in the production it has the prominence in spite of poor crops and the low productivity of animals.Polish farming is predestined for manufacturing large amounts of good quality of some products to meet needs of the domestic and the E.U. market (e.g. rye, potatoes, apples and the concentrate of the apple juice, soft fruit, vegetables and their preserves, cultivated mushrooms, milk and its preserves and many others).
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 1, s. 361-365